Workshop Identifikasi Hoaks dan Berita Palsu Untuk Peningkatan Literasi Digital Siswa SMPN 13 Pontianak - Primi Wulan, Adisti; Ashadi Alimin, Al; Uli, Indriana; Lizawati; Leni Mastuti, Dewi (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This Community Service activity was carried out at SMP Negeri 13 Pontianak, West Kalimantan, based on the growing exposure of misleading information that students can easily access in the current digital era. Students at the lower secondary school level are in an early adolescent transition phase, making them vulnerable to receiving and distributing information without having adequate skills to assess its reliability. The activity aimed to raise awareness of the risks of false information, introduce ways to evaluate the quality of information through considerations of timeliness, content relevance, source authority, data accuracy, and communicative purpose, and develop critical thinking skills in understanding various digital content they encounter. The implementation consisted of interactive presentations, group discussions, simulated video viewing, hands-on practice using fact-checking sites, and the creation of digital campaign posters as practical application. All activities carried out on April 25, 2025 were attended by 33 students divided into small groups to facilitate guidance. The results showed a significant improvement in digital literacy skills, indicated by an increase in the average understanding score from 67.88 at the beginning to 90.00 at the end. Each group successfully produced a digital campaign poster that was published through the school’s social media as a form of contribution to promoting responsible information sharing. The main outputs, including the final report and published news coverage, were completed, while additional outputs such as a submitted scientific article and a copyrighted digital module were also produced. This activity demonstrates that engaging students directly in training strengthens their critical awareness and encourages active participation in nurturing a healthier information ecosystem.